The Development of the Film Industry in Saudi Arabia 2005–2020 - ALAMRI, MUSAB (2022)
This thesis explores the development of the film industry in Saudi Arabia from 2005 to 2020. It divides the industry’s development in Saudi Arabia into two periods: from 2005 to 2015 and from 2015 to 2020. In the first period, the industry was supported and led by two key industry figures, the Rotana Group and the Saudi Film Festival (SFF). The second period was characterised by the government and non-profit organisations leading the industry’s development through the Saudi Film Council (SFC), General Commission for Audiovisual Media (GCAM) and King Abdulaziz Center for World Culture (Ithra). This thesis includes personal interviews with industry decision-makers and leaders such as the CEO of SFC, founder and CEO of the SFF and the Head of the Cinema Department at Ithra Centre. This thesis contributes to the knowledge of the Saudi Arabian film industry through a comprehensive analysis of the industry structures that can support the industry’s growth, enabling government agencies, non-profit organisations and cultural institutions to better support its further development. The findings reveal that religious opposition to cinema led to its decline after 1979, and in the first time period, this opposition limited Rotana’s ability to produce more films and closed its theatres. Events in the second time period demonstrate the government’s seriousness about supporting the industry and its growth, and the government has established a massive financing policy for local and foreign films produced inside Saudi Arabia. Nevertheless, the challenges of censorship still trouble film producers, especially for domestic films, whereas foreign films have greater freedom although the executive regulations for censorship do not differentiate between foreign and domestic films. Overall, this thesis aims to answer the question: What is meaningful about the Saudi film industry’s development in the twenty-first century?